Mathematical Modeling of a Unicycle Robot and Use of Advanced Control Methodologies for Multi-Paths Tracking Taking into Account Surface Friction Factors - Basal, Mohamed Abdelhakim; Ahmed, Mohammed Fadhil (Universitas Muhammadiyah Yogyakarta, 2025)
The research aims to design robust controllers that achieve the stability of a single-wheeled robot under the presence of friction factors and to track different parameters to verify robust stability. This paper presents a new study of the unicycle robot system that is controlled using advanced control methodologies. The paper aims to improve the work of the unicycle robot system, due to its effective impact on improving the performance of driving the robot, which is reflected in the smoothness of the vehicle speed change, ensuring the stability of the robot and the safety of the investor in the uncertain work environment. The main goal is to achieve high dynamic performance for the unicycle robot system. The studied system is non-linear and is subject to the restrictions of the friction factor change with the speed change of the unicycle robot. What increases the difficulty of controlling this type of control system is the uncertainty of some parameters of the control system, such as friction factors. In this paper, two advanced control methodologies were proposed: the optimal controller and the optimal parametric controller. The research results showed that both the optimal and optimal parametric controllers succeeded in achieving stability despite the uncertainty of the parameters and multiple friction factors, but with a relative superiority of the optimal parametric controller. Previous research has discussed many controllers such as classical and advanced controllers such as sliding control and fuzzy control, but it has not previously dealt with the optimal parametric controller that will be discussed in this research.